Andean Nº10 - César Leonardo Munive Carrión (2024)
The tenth issue focuses on ethics as a fundamental pillar of social life and organizational management. The content explores the urgent need for a new paradigm in bioethics that goes beyond the purely biomedical to focus on the protection of life from the perspective of “good living.”The journal also explores the intersection between ethics and literature, pays tribute to academic careers such as that of Carlos Landázuri, and presents new publications from the Universidad Andina Simón Bolívar on topics of inclusive entrepreneurship, social cohesion, and health.
Keywords: Ethics; Citizenship; Bioethics; Algorithms; AI